PERAN ETIKA BISNIS ISLAM DALAM MENCEGAH KECURANGAN PRODUSEN DAN MEMBANGUN KEPERCAYAAN KONSUMEN - Farah Naila Mufidah; Muhamad Abdul Gofur; Naela Soraya (Media Riset Bisnis Manajemen Akuntansi, 2025)
This research delves into the significance of Islamic business ethics in cultivating consumer trust within the contemporary business landscape. Emphasizing principles like honesty, justice, trustworthiness, and transparency rooted in sharia law, Islamic business ethics aims to foster a just and sustainable economic framework. Through a descriptive qualitative analysis drawing on a literature review, the study highlights how adhering to Islamic values such as tawhid, knowledge, justice, responsibility, freedom, benevolence, and the distinction between halal and haram can curb fraudulent behaviors and enhance consumer loyalty. Findings demonstrate that companies embracing Islamic business ethics not only steer clear of legal infractions and reputational harm but also bolster consumer relationships based on trust and continued satisfaction. Thus, integrating Islamic business ethics serves as a cornerstone for ethical, competitive, and divinely favored business operations.Keywords : Islamic bussines ethics, consumer trust, sharia principles, ethical bussines